2019
DOI: 10.1016/j.jogc.2018.05.042
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Barriers to Vaccination During Pregnancy in the Canadian Context

Abstract: Objective: While vaccination in pregnancy has the potential to dramatically impact maternal and infant morbidity and mortality, uptake of recommended vaccinations in pregnancy remains low. Our objective was to identify barriers and facilitators of vaccination during pregnancy in Canada. Methods: The MEDLINE database, as well as the table of contents of four relevant Canadian journals were screened to identify all studies that considered barriers and/or facilitators to vaccination during pregnancy, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Previous reviews have established a narrative of evidence that suggests a broad range of factors (vaccine cost, accessibility, maternal knowledge, social influences, context, healthcare professional (HCP) recommendation and the perception of risks and benefits) all contribute to vaccine uptake. Consensus within the field and across four prior literature reviews indicate that receiving a recommendation from an HCP for vaccination is the most important factor in maternal decision-making, irrespective of geographic or social context [11][12][13][14][15]. In general, there is limited data on maternal vaccination uptake and records of HCP recommendations at a national level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews have established a narrative of evidence that suggests a broad range of factors (vaccine cost, accessibility, maternal knowledge, social influences, context, healthcare professional (HCP) recommendation and the perception of risks and benefits) all contribute to vaccine uptake. Consensus within the field and across four prior literature reviews indicate that receiving a recommendation from an HCP for vaccination is the most important factor in maternal decision-making, irrespective of geographic or social context [11][12][13][14][15]. In general, there is limited data on maternal vaccination uptake and records of HCP recommendations at a national level.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature and systematic reviews tend to characterize the factors influencing maternal vaccination decisions as either barriers or facilitators [11][12][13][14][15]. We sought to quantify the association between beliefs, attitudes and prior behaviours that influence maternal vaccination uptake.…”
Section: Introductionmentioning
confidence: 99%
“…This can partly be attributed to limited knowledge among pregnant women, their poor attitude about immunization, their failure to attend all ANC visits, lack of training of the Village Health Teams (VHTs) on the importance of TT vaccination for pregnant mothers, limited health education to pregnant mothers, and maternal vaccine safety concerns. Studies have shown that healthcare providers [16,17], knowledge of patient and provider [18], improved ANC attendance and surveillance systems [17,19] play an important role in maternal vaccination uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying determinants of influenza vaccine uptake in pregnancy may help target education efforts and intervention strategies to most efficiently promote vaccination in pregnancy. Previous studies have identified patient-level factors associated with acceptance of influenza vaccination during pregnancy in Canada, including perception of disease susceptibility and severity, perception of benefits—including safety and effectiveness—of vaccination, being cared for in pregnancy by a family practitioner, greater knowledge about influenza and vaccinations, and demographic factors including multiparity, comorbidities, higher income, higher education, married status, and older maternal age (Poliquin et al, 2019). Some studies have applied the health belief model (Bettinger et al, 2016; Fabry et al, 2011), but most have not been theory driven, instead using cross-sectional data to identify demographic factors associated with vaccination (Brien et al, 2012; Gracie et al, 2011; Hilderman et al, 2011; Legge et al, 2014; Liu et al, 2012; Yudin et al, 2009), or exploring of the knowledge, attitudes, and beliefs of mothers (Halperin et al, 2014; Kowal et al, 2015), practitioners (Desjardins et al, 2017; Lee et al, 2005), or both (Tong et al, 2008).…”
mentioning
confidence: 99%